2021
DOI: 10.1186/s41938-021-00401-w
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo biological control of the green mold using different bacteria in button mushroom cultivation

Abstract: Background Aggressive biotype (Trichoderma aggressivum f. aggressivum) of green mold is one of the main biotic factors limiting button mushroom (Agaricus bisporus) cultivation. Due to issues such as fungicide resistance, cost, and adverse effects, biological control seems to be an applicable management method against the green mold in button mushroom cultivation. Results The objective of the study was to assess biological control of green mold in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Wang et al [34] reported that metabolites of different Trichoderma species inhibited the growth of L. edodes mycelium, and its hyphae were distorted and swollen in vitro. A number of Bacillus and Streptomyces isolates proved to be efficient in suppressing the growth of mushroom pathogenic Trichoderma strains [70][71][72]81,82]. Moreover, a broad range of plant extracts, essential oils and compost teas were also found to sufficiently inhibit different fungal pathogens of mushrooms, including Trichoderma species [73], suggesting the possibility of involving these agents in IPM approaches to successfully combat mushroom green mould disease.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [34] reported that metabolites of different Trichoderma species inhibited the growth of L. edodes mycelium, and its hyphae were distorted and swollen in vitro. A number of Bacillus and Streptomyces isolates proved to be efficient in suppressing the growth of mushroom pathogenic Trichoderma strains [70][71][72]81,82]. Moreover, a broad range of plant extracts, essential oils and compost teas were also found to sufficiently inhibit different fungal pathogens of mushrooms, including Trichoderma species [73], suggesting the possibility of involving these agents in IPM approaches to successfully combat mushroom green mould disease.…”
Section: Discussionmentioning
confidence: 99%
“…The role of bacterial activities in defensive responses to pathogens or the promotion of mycelia and mushroom growing has been studied. Aydo gdu et al [160] found that B. subtilis, Stenotrophomonas maltophilia, Pseudomonas rhodesiae, and B. amyloliquefacie inhibited the growth of the green mold Trichoderma aggressivum, as well as A. bisporus, in vitro. Cho et al [143] isolated fluorescent Pseudomonas spp.…”
Section: Microbial Community Influence On Mushroom Cultivationmentioning
confidence: 99%
“…In this way, a casing soil layer in 3.5 to 4 cm thickness was formed on the compost. Afterwards, 1 mL green mould inoculum (spore suspension; 1 × 10 6 conidia/mL) per bag was injected into central part of the casing soil using a syringe (Aydoğdu et al, 2021). One day later, three doses of each disinfectant listed below were separately applied to the casing soil in each bag in the treatments.…”
Section: Disinfectant Treatmentsmentioning
confidence: 99%